Kocuria rhizophila Adds to the Emerging Spectrum of Micrococcal Species Involved in Human Infections - Becker, Karsten (American Society for Microbiology (ASM), 2008)
We describe the first case of a Kocuria rhizophila infection in a boy with methylmalonic aciduria. A single clone was isolated from blood samples drawn through a port system and from peripheral veins during septic episodes within a 2-year period. K. rhizophila expands the emerging number of “micrococci” considered to be etiologically relevant.